PMO-156 Plasma HBsAG levels correlate with liver cccDNA in tolerant children with infancy acquired chronic hepatitis B infection. (28th May 2012) - Carey, I; Zen, Y; Bruce, M J; Horner, M; Bansal, S; Vergani, D; Mieli-Vergani, G
Abstract : Introduction: Plasma HBsAg reflects the transcriptional activity of covalently closed circular (ccc) DNA within the liver rather than the absolute amount of cccDNA copies. Higher plasma HBsAg levels are reported among tolerant than immuno-active HBeAg positive chronic hepatitis B (CH-B) patients. Only limited information is available on the interaction of plasma HBsAg, expression of HBsAg and HBcAg within the liver and liver relaxed circular (RC) HBV DNA and cccDNA in patients with infancy-acquired CH-B. Aims: To evaluate whether there is a relationship between plasma HBsAg and HBV DNA levels and HBsAg/HBcAg expression within the liver and liver RC HBV DNA and cccDNA in tolerant children with infancy-acquired CH-B. Patients: 23 children (eight males, median age 10.2 yrs) with infancy-acquired CH-B (all HBeAg+) in tolerant stage underwent liver biopsy prior to antiviral therapy with lamivudine and interferon-α. Methods: Plasma HBsAg and HBV DNA levels were measured at therapy baseline by Abbott ARCHITECT® assay and real-time TaqMan PCR [both log10 IU/ml]. Baseline liver RC HBV DNA and cccDNA was quantified by real-time TaqMan PCR [copies/ng genomic DNA]. Immunostaining of formalin-fixed, paraffin-embedded liver specimens assessed HBsAg and HBcAg expression [# of positive cells per 1000 hepatocytes]. Results are presented as median, range. Results: Baseline plasma HBsAg levels were 4.67 (3.7–5.1), HBV DNA was 8.2 (7.1–8.9) both log10 IU/ml and ratio HBsAg/HBV DNA 0.57 (0.44–0.65). Liver RC HBV DNA was 4.41 (2–5.3) log10 copies/ng genomic DNA and cccDNA was 363 (0.3–3632) copies/ng genomic DNA. HBsAg is predominantly expressed in cytoplasm focally associated with membranous staining, 2.9 (0–56.9) positive cells/1000 hepatocytes, in contrast to HBcAg expressing predominantly in the nucleus, 8.3 (0.5–83.6) positive cells/1000 hepatocytes. There were positive bivariate Spearman correlations between plasma HBsAg levels and liver cccDNA (r=0.41, p=0.05), HBcAg liver expression and cccDNA (r=0.44, p=0.05), liver RC HBV DNA and cccDNA (r=0.67, p=0.04) and a trend towards correlation between plasma HBsAg and HBsAg liver expression (r=0.38, p=0.07). Conclusion: Plasma HBsAg levels correlate with liver cccDNA in tolerant children with infancy-acquired chronic hepatitis B infection suggesting that plasma HBsAg levels acts as a surrogate marker of cccDNA within the liver in tolerant patients. Competing interests: I Carey grant/research support from: BMS, Gilead, Y Zen: None declared, M Bruce: None declared, M Horner: None declared, S Bansal: None declared, D Vergani: None declared, G Mieli-Vergani: None declared.